Effect of Macroeconomics, Capital, Governance on Earnings, Risk, Yield to Maturity, with Bond Rating Moderation in Banks - Valdo Hana Primasatria; Tri Ratnawati; Ida Ayu Sri Brahmayanti (Harmony Management: International Journal of Management Science and Business, 2025)
This study aims to analyze the influence of macroeconomic conditions, capital, and good corporate governance on earnings, financial risk, and yield to maturity bond, with bond rating acting as a moderating variable. The research focuses on banking companies listed on the Indonesian Stock Exchange (IDX). A Quantitative approach with a secondary data from Indonesian Stock Exchange (IDX) and Indonesian Bond Market Directory (IDMB) Purposive sampling method was applied, resulting in 102 active banking bond samples listed on the IDX during the 2020–2023 period. The hypotheses were tested using Structural Equation Modeling with Partial Least Squares (SEM-PLS). Out of 14 proposed hypotheses, 4 were supported with statistically significant results, while the remaining 10 were not. The results show that capital has a significant effect on financial risk, while earnings significantly influence both financial risk and bond yield to maturity. Overall, this study shows that internal factors like earnings and capital have a stronger impact on a company’s risk perception and debt cost than implementation good corporate governance and macroeconomic conditions. It also highlights the important role of bond ratings in reflecting a company’s reputation and credit quality in the banking bond market.